Rick [large type] - Gino, Alex (Thorndike Press, a part of Gale, a Cengage Company, 2020)
Eleven-year-old Rick Ramsey has generally gone along with everybody, just not making waves, even though he is increasingly uncomfortable with his father's jokes about girls, and his best friend's explicit talk about sex; but now in middle school he discovers the Rainbow Spectrum club, where kids of many genders and identities can express themselves--and maybe among them he can find new friends and discover his own identity, which may just be to opt out of sex altogether.